Childhood pneumococcal meningitis: may it begin with diarrhea and proceed with cerebral infarct? (Bangladesh Journal of Medical Science, 2011)
Pneumococcal meningitis does continue to be an important cause of mortality and morbidity in childhood despite widespread vaccination. It develops thorough invasion of the meninges by the agent via bloodstream. It may manifest typical signs of meningeal irritation and even the symptoms not belonging to the central nervous system, such as diarrhea. The diagnosis is made by microscopic evaluation and culture of cerebrospinal fluid (CSF) obtained by lumbar puncture. Despite the treatment, the risk of occurrence of cerebral and neurologic complications is high. A two-month old baby girl was presented to our outpatients' clinic because of fever and diarrhea; she was diagnosed with pneumococcal meningitis and developed cerebral infarct during surveillance. The reason why we presented this patient is to highlight that meningitis due to pneumococ, one of the most common causing agents in childhood meningitis, may have clinical presentations other than expected. Key words: Pneumococcal meningitis; cerebral infarct; infant.  DOI: 10.3329/bjms.v10i1.7320 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.52-56